91.3k views
4 votes
What is the simplest form 0f 2√2/√3-√2

User Doblak
by
4.8k points

2 Answers

6 votes

Answer:


4+2√(6)

Explanation:

Given expression is
(2√(2))/(√(3)-√(2)).

Now we need to simplify this. So multiply and divide by conjugate of denominator.


(2√(2))/(√(3)-√(2))


=(2√(2))/(\left(√(3)-√(2)\right))


=(2√(2))/(\left(√(3)-√(2)\right))\cdot(\left(√(3)+√(2)\right))/(\left(√(3)+√(2)\right))


=(2√(6)+2√(4))/(\left(√(3)\right)^2-\left(√(2)\right)^2)


=(2√(6)+2\cdot2)/(3-2)


=(2√(6)+4)/(1)


=2√(6)+4


=4+2√(6)

Hence final answer is
4+2√(6).

User Sean Taylor
by
5.4k points
2 votes

Answer:


(2√(2))/(√(3)-√(2))=2√(6)+4

Explanation:

We have the expression:


(2√(2))/(√(3)-√(2))

To simplify the expression multiply by the conjugate of the denominator.

The denominator is


√(3)-√(2)

Then its conjugate is:


√(3)+√(2)

Then:


(2√(2))/(√(3)-√(2))*(√(3)+√(2))/(√(3)+√(2))\\\\=(2√(2)√(3)+2√(2)√(2))/((√(3))^2-(√(2))^2)\\\\(2√(6)+4)/(3-2)}\\\\= (2√(6)+4)/(1)}=2√(6)+4

User TheBoubou
by
5.4k points